Comparative re site study of human tumor susceptibility gene 101 (TSG101) found among different human tissue types - Anusyah, Rathakrisnan (Universiti Malaysia Sarawak, UNIMAS, 2007)
There are many genes that encode proteins for cell proliferation, differentiation, and development. Mutations in these genes can affect its function. Accumulation of genetic alteration through mutations or epigenetic event plays an important role in cancer progression. One such gene presumed to be linked to cancer is the Tumor Susceptibility Gene 101 (TSG101). However, many research studies failed to detect genomic alteration in this gene yet these studies have shown that the TSG101 undergoes alternative and aberrant splicing. Therefore, this study was proposed to detect whether the nucleotide variations and/or mutations of the TSG101 diverge in different human tissue types via restriction site characterization. Besides that, it is also to observe whether any of the nucleotide variations dominate certain cancer types. Briefly, total RNA from nasopharyngeal carcinoma, oral carcinoma and bladder carcinoma was transcribed into cDNA prior proceeding to polymerase chain reaction (PCR) using several sets specific of TSG101 primer. Subsequently, the PCR product was purified and subjected to restriction enzyme digestion. Agarose gel electrophoreses analysis of TSG101 partial sequence indicated that there is no mutation found at the specific restriction site in all tissues samples studied. Hence, mutational alteration might not be the main event in all the cancer studied. Nevertheless, sequencing of the TSG101 full length will provide more accurate and reliable results. Epigenetic studies of TSG101 can be considered to further elucidate the genetic alteration of this gene that leads to cancer.